2015
DOI: 10.1111/den.12511
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease after peroral endoscopic myotomy: Analysis of clinical, procedural and functional factors, associated with gastroesophageal reflux disease and esophagitis

Abstract: Preoperative, perioperative or postoperative factors minimally correlated with GERD after POEM. Clinically relevant GERD was identified in less than one-third of patients, but all patients were well controlled with medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 49 publications
(130 reference statements)
6
61
2
1
Order By: Relevance
“…Familiari et al 26 identified that a lower IRP was associated with heartburn after POEM. Patient demographics, including age, body mass index, sigmoid oesophagus and previous therapies, did not significantly increase the risk of developing GORD.…”
Section: Discussionmentioning
confidence: 99%
“…Familiari et al 26 identified that a lower IRP was associated with heartburn after POEM. Patient demographics, including age, body mass index, sigmoid oesophagus and previous therapies, did not significantly increase the risk of developing GORD.…”
Section: Discussionmentioning
confidence: 99%
“…Familiari et al reported that in 50.5% patients, abnormal acid exposure was found and clinically relevant GERD was evident in 29.1%. Esophagitis and symptoms resolved completely with proton pump inhibitor (30).…”
Section: Efficacy and Complicationmentioning
confidence: 95%
“…Hasta la fecha, solo cuatro series han presentado datos sustanciales sobre la evaluación de la ERGE en sus pacientes utilizando los tres métodos (evaluación sistemática de los síntomas, evaluación endoscópica y estudio ambulatorio de pH) 18,19 . Estos estudios hallaron que el 27-59% de los pacientes tenía signos endoscópicos de reflujo (principalmente esofagitis leve clase A o B de Los Ángeles), el 29-38% tenía anormalmente elevada la exposición al ácido en los estudios de pH y el 15-23% tenían los síntomas frecuentes de reflujo gastroesofágico 20,21 .…”
Section: El Poem Y La Enfermedad Por Reflujo Gastroesofágicounclassified